2020
DOI: 10.5334/aogh.2663
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Diabetes Mellitus in Hosanna Town, Southern Ethiopia

Abstract: Background/Objectives: Diabetes is a global public health problem, and its burden is rising, particularly in developing countries. However, limited data is available from sub-Sahara African communities to assess and monitor the disease burden. The study aimed to determine the prevalence and associated factors of diabetes in Hosanna, Ethiopia. Methods: A community-based cross-sectional study was conducted among 634 randomly selected adults in Hosanna. The study participants were recruited by multi-stage stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
39
5

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 30 publications
8
39
5
Order By: Relevance
“…The pooled meta-regression analysis revealed a statistically significant difference in the exposure of type-2 DM among normal body mass index and obese with the odds ratio of 1.54 (95%: CI: 1.3, 1.83). Among the studies included in this meta-analysis, older age individuals were more exposed to type-2 diabetes than the younger age group, which is supported by the study 1 , 2 , 5 , 9 , 17 , 18 , 20 , 22 – 24 , 26 , 28 , 32 , 33 , 38 , 51 , 56 . In contrast, our study 11 , 23 , 35 , 45 had got the result that contradict the other studies and concluded age had no any effect over the development of DM.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…The pooled meta-regression analysis revealed a statistically significant difference in the exposure of type-2 DM among normal body mass index and obese with the odds ratio of 1.54 (95%: CI: 1.3, 1.83). Among the studies included in this meta-analysis, older age individuals were more exposed to type-2 diabetes than the younger age group, which is supported by the study 1 , 2 , 5 , 9 , 17 , 18 , 20 , 22 – 24 , 26 , 28 , 32 , 33 , 38 , 51 , 56 . In contrast, our study 11 , 23 , 35 , 45 had got the result that contradict the other studies and concluded age had no any effect over the development of DM.…”
Section: Resultssupporting
confidence: 61%
“…In this sub-categorical meta-analysis, eleven studies were included to examine the effect of body mass index on type-2 DM 16 , 17 , 19 , 21 , 27 , 31 , 34 , 36 , 40 , 44 , 48 , 49 . Of these, seven studies indicated a statistically significant association between body mass index and type-2 17 , 19 , 21 , 31 , 34 , 43 , 49 that shows a high risk of DM as body mass increased. In comparison, four studies showed there was no statistical difference in type-2DM among the normal weight and overweighed 17 , 27 , 36 , 46 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, different pieces of evidence including our study supported that the risk of occurrence of DM was significantly higher among older age groups compared to younger age groups. 17,33,[37][38][39][40] Conversely, the increased prevalence of DM in Pakistan study might be due to the use of Oral Glucose Tolerance Test (OGTT) and HbA1c for diagnoses DM in addition to FBG and RBG which used in our study. This might be amplified the detection rate of diabetes mellitus in the case of Pakistan's study.…”
Section: Discussionmentioning
confidence: 79%
“…1). Of the 23 articles reported, 11 were from Ethiopia [28][29][30][31][32][33][34][35][36][37][38], Three from Ghana [39,40], and the remaining eight studies from Sudan [41], Benin [42], Botswana [43], Egypt [44], Burkina Faso [45], Zambia [46],Tunisia [47] and South Africa [46].…”
Section: Identification and Description Of Studiesmentioning
confidence: 99%